2012
DOI: 10.1111/j.1365-3040.2012.02523.x
|View full text |Cite
|
Sign up to set email alerts
|

The bHLH transcription factor MdbHLH3 promotes anthocyanin accumulation and fruit colouration in response to low temperature in apples

Abstract: Low environmental temperatures promote anthocyanin accumulation and fruit colouration by up-regulating the expression of genes involved in anthocyanin biosynthesis and regulation in many fruit trees. However, the molecular mechanism by which fruit trees regulate this process in response to low temperature (LT) remains largely unknown. In this study, the cold-induced bHLH transcription factor gene MdbHLH3 was isolated from an apple tree and was found to interact physically and specifically through two regions (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
494
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 589 publications
(507 citation statements)
references
References 62 publications
12
494
1
Order By: Relevance
“…The recombinant pRI101-GFPMdMYC2 construct was introduced into apple calli as previously described (Xie et al, 2012), and the transgenic calli were used for co-IP analysis. The procedures for co-IP were as previously described (Li et al, 2016).…”
Section: Co-ip Assaymentioning
confidence: 99%
“…The recombinant pRI101-GFPMdMYC2 construct was introduced into apple calli as previously described (Xie et al, 2012), and the transgenic calli were used for co-IP analysis. The procedures for co-IP were as previously described (Li et al, 2016).…”
Section: Co-ip Assaymentioning
confidence: 99%
“…However, the observations on GFP-MYB27 stability, along with the finding that phosphorylation of At-MYBL2 in Arabidopsis prevents its degradation (Ye et al, 2012), suggest protein levels of the active repressors are subject to strong posttranslational regulation. Posttranslational regulation has also been reported for the flavonoid related bHLH and R2R3-MYB activators of Arabidopsis (Maier et al, 2013;Patra et al, 2013) and for an anthocyanin related bHLH in apple (Malus domestica) (Xie et al, 2012), indicating cross-species conservation of this aspect of the regulatory network.…”
Section: An Integrated Model For Anthocyanin Regulation In Eudicotsmentioning
confidence: 99%
“…These include the posttranslational modifications of the TFs that regulate anthocyanin biosynthesis (Xie et al, 2012;Ye et al, 2012;Maier et al, 2013;Patra et al, 2013), chromatin remodeling (Hernandez et al, 2007), and the identification of repressor proteins that limit expression of the anthocyanin biosynthetic genes (Aharoni et al, 2001;Dubos et al, 2008;Matsui et al, 2008;Yuan et al, 2013). Two distinct classes of MYB TFs have been identified that can limit anthocyanin production: R3-MYBs and R2R3-MYB repressors, which have one or two repeats of the MYB domain region, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Full-length cDNAs of MdCOP1-1 and MdCOP1-2, as well as an MdMYB1 fragment as described by Xie et al (2012), were inserted into pGAD424 and pGBT9 (Clontech). All of the constructs were transformed into yeast strain AH109 using a lithium acetate method.…”
Section: Yeast Two-hybrid Assaysmentioning
confidence: 99%